Simulation of the Effect of Artificial Water Transfer on Carbon Stock of Phragmites australis in the Baiyangdian Wetland, China. (28th February 2017) - Chen, Xinyong; Wang, Fengyi; Lu, Jianjian; Li, Hongbo; Zhu, Jing; Lv, Xiaotong
Abstract : How to explain the effect of seasonal water transfer on the carbon stocks of Baiyangdian wetland is studied. The ecological model of the relationship between the carbon stocks and water depth fluctuation of the reed was established by using STELLA software. For the first time the Michaelis-Menten equation (1) introduced the relation function between the water depth and reed environmental carrying capacity, (2) introduced the concept of suitable growth water depth, and (3) simulated the variation rules of water and reed carbon stocks of artificial adjustment. The model could be used to carry out the research on the optimization design of the ecological service function of the damaged wetland.